Anticipated and Unanticipated Wage Changes, Wage Risk, and Intertemporal Labor Supply - Pistaferri, Luigi (Journal of Labor Economics, 2003)
In this article, I estimate how labor supply responds to anticipated wage growth, unanticipated wage growth, and wage risk using the 198993 panel section of the Bank of Italy Survey of Households' Income and Wealth (SHIW), which collects individual expectations of future wages. The use of subjective expectations has several advantages. First, they provide information on the evolution and riskiness of future wages that the econometrician may never hope to observe. Moreover, this avoids the need for specifying instruments for the growth rate of wages. Finally, forecast errors can be directly controlled for, thus avoiding inconsistency in short panels.